2017
DOI: 10.3727/096504017x14865126670075
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA LINC0086 Functions as a Tumor Suppressor in Nasopharyngeal Carcinoma by Targeting miR-214

Abstract: Nasopharyngeal carcinoma (NPC) is a distinct head and neck cancer, which is occurring at a high frequency in Southern China. Emerging studies have shown that long noncoding RNAs (lncRNAs) play a critical role in carcinogenesis and progression. In this study, we established a comprehensive lncRNA profile in NPC and found that 35 lncRNAs were differentially expressed in NPC. We found that LINC0086 was decreased in NPC patient serum samples and tissues. The Kaplan-Meier survival curve showed that patients with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Others reported that miR-214 mediated the inhibiting effect of FOXD3 on proliferation, invasion and metastasis by targeting MED19 in colon cancer (44). Moreover, miR-214 acted as a target of LncR-LINC0086 and overexpressed miR-214 reversing the suppressive effects of LINC0086 on nasopharyngeal carcinoma (NPC) growth in vitro and in vivo (45). Generally, miRNA is regulated by the upstream transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Others reported that miR-214 mediated the inhibiting effect of FOXD3 on proliferation, invasion and metastasis by targeting MED19 in colon cancer (44). Moreover, miR-214 acted as a target of LncR-LINC0086 and overexpressed miR-214 reversing the suppressive effects of LINC0086 on nasopharyngeal carcinoma (NPC) growth in vitro and in vivo (45). Generally, miRNA is regulated by the upstream transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence have shown that lncRNAs function as oncogenic or suppressor genes in multiple cancers, involving in transcription and post‐transcription regulation (Guo, Ma et al, ; He et al, ). In present study, our team performed series of experiments to investigate the biological role of lncRNA SNHG15 on non‐small‐cell lung cancer (NSCLC) tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…LINC0086 showed to decrease in miR-214 expression by directly interacting with miR-214 in the 3’-UTR region. Furthermore, the reduced LINC0086 on cell growth of NPC were reversed by exogenously expressed miR-214 in vitro and in vivo suggesting a potential new diagnostic and therapeutic biomarker for NPC [59]. LOC401317 was highly induced by p53 transgene expression.…”
Section: Tumor Suppressor Lncrnasmentioning
confidence: 99%
“…These observations indicated a pivotal role for lncRNA-LET in NPC cell proliferation. The expression of lncRNA LINC0086 was also reduced in NPC, resulting in increased proliferation and decreased apoptosis in NPC cells [59]. LINC0086q expression was associated with histological grades, lymph node metastasis, and clinical stages in patients with NPC.…”
Section: Tumor Suppressor Lncrnasmentioning
confidence: 99%